Study on the composition of municipal solid waste in Mahkota Aman residential area - Muhammad Amirul , Miskon (2012)
Nowadays, Municipal Solid Waste is the biggest environmental problem in Malaysia. The amount generated of the waste continues to increase in response to rapid increase in population, accelerated urbanization and industrialization process. The study on Municipal Solid Waste is important in order to determine and evaluate their composition and characteristic. With the obtained data, municipal solid waste can be managed with more efficiency. This research is carried out by segregating and weighing solid waste in residential area. Objectives of the study are to collect data of solid waste composition and physical characteristic, determine solid waste generation and analyze relationship affecting the solid waste generation. Data obtained from weighing and segregating the solid waste will be calculated manually. In the end of this study, we will get the result on highest composition of solid waste at the residential area and also the time when the production, of solid waste is at their peak. From this research, it hope that can be a good help in order for us to manage solid waste better for Malaysia.